2020
DOI: 10.1186/s12916-020-01516-x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent polycystic ovary syndrome according to the international evidence-based guideline

Abstract: Background: Diagnosing polycystic ovary syndrome (PCOS) during adolescence is challenging because features of normal pubertal development overlap with adult diagnostic criteria. The international evidence-based PCOS Guideline aimed to promote accurate and timely diagnosis, to optimise consistent care, and to improve health outcomes for adolescents and women with PCOS. Methods: International healthcare professionals, evidence synthesis teams and consumers informed the priorities, reviewed published data and syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
232
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(290 citation statements)
references
References 123 publications
3
232
1
2
Order By: Relevance
“…This limited our ability to systematically review the literature; however, this has been a common problem when evaluating any aspect of PCOS during adolescence, as highlighted by the recent international evidence-based guidelines. 12,13 An additional limitation of this review was the fact that the studies used multiple diagnostic criteria to diagnose the adolescent girls with PCOS, two studies did not specify diagnostic criteria and only one study reported on age of menarche, which is an important factor to determine menstrual irregularity (one of the diagnostic criteria for PCOS). Despite this, most of the studies (n = 6) used commonly accepted criteria, including menstrual irregularity and hyperandrogenism, 24,25,28,29,31,34 and only three studies 26,30,33 used Rotterdam criteria, 6 including pelvic ultrasound, which is no longer recommended for diagnosis of PCOS until 8 years post-menarche.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This limited our ability to systematically review the literature; however, this has been a common problem when evaluating any aspect of PCOS during adolescence, as highlighted by the recent international evidence-based guidelines. 12,13 An additional limitation of this review was the fact that the studies used multiple diagnostic criteria to diagnose the adolescent girls with PCOS, two studies did not specify diagnostic criteria and only one study reported on age of menarche, which is an important factor to determine menstrual irregularity (one of the diagnostic criteria for PCOS). Despite this, most of the studies (n = 6) used commonly accepted criteria, including menstrual irregularity and hyperandrogenism, 24,25,28,29,31,34 and only three studies 26,30,33 used Rotterdam criteria, 6 including pelvic ultrasound, which is no longer recommended for diagnosis of PCOS until 8 years post-menarche.…”
Section: Discussionmentioning
confidence: 99%
“…Research including larger sample sizes of better-defined populations, as recently described, is required in adolescent girls with PCOS, but further research in the area of emotional well-being is also required. 12 Additionally, research in QoL with a focus on normal BMI in adolescent girls with PCOS compared to healthy adolescent girls is necessary to draw clearer conclusions about the impact of the condition irrespective of the influences of an overweight or obese BMI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stein and Leventhal who were firstly linked between PCOS and obesity in 1935 when 3/7 of first PCOS diagnosed patients were obese (3). The main features of this syndrome are oligo/anovulation, and disturbance in androgen hormones leading to different ranges of hirsutism, weight gain, acne, and amenorrhea according to Rotterdam criteria (4,5). Overweight or being obese with body mass index (BMI) greater than 30 kg/m 2 is a vigorous risk factor leading to PCOS women in around the age of 30 (5,6,7), in addition to represent a risk factor to cardiovascular disease, diabetes mellitus type 2, hypertension and several types of cancers (8).…”
Section: Introductionmentioning
confidence: 99%